Advances in nondestructive evaluation : proceedings of the 11th Asian Pacific Conference on Nondestructive Testing, Jeju Island, Korea, 3-7 November 2003 - Lee, Seung-Seok (Trans Tech Publications, 2004)
The aim of this 3-volume set is to bring together the expertise of scientists and engineers, in academia and industry, who are active in the field of non-destructive testing and evaluation. The papers cover activities which include analytical techniques as well as experimental case studies. The set consists of over 390 papers, including three plenary papers: An Assessment of the Current State and Future Challenges in Quantitative NDE by R. Bruce Thompson, Ultrasonic Characterization of Thin Film Material Constants and Defects by Jan D. Achenbach and Ultrasonic Guided Waves in Structural Health Monitoring by Joseph L. Rose. The headings of the various sections are: Materials Characterization, Signal and Image Processing, Ultrasonics, Guided Waves, Acoustic Emission, Eddy Current Testing, EMAT, Magnetic Methods, Optical Methods, NDE in the Electronics Industry, Industrial Applications, NDE in Agriculture, Microsensor/MEMS/Nano, Fatigue and Fracture, Radiography and Neutron Radiography, Acoustics and Vibration, Civil Infrastructure, Personnel Qualifications and Standards, Reliability, Composite Materials and Structures, Health Monitoring, Bio and Medical NDE, Smart Materials and Structures, Nuclear Industry, Welding.
Keywords: Nondestructive testing -- Congresses.; elektronické knihy; electronic books